Pediatric bone health in the community: Caretaker comprehension - Ritt Givens, BS; Jamie Bousleiman, BA; Mark M. Herbert, BS; Afrain Z. Boby, MS; Kevin Lu, MA; Adrienne M. Koder, DO; Katherine A. Rosenwasser, MD; Prakash Gorroochurn, PhD; Christen M. Russo, MD (Elsevier, 2024)
ABSTRACT: Background: The physiological importance of calcium and vitamin D intake, specifically in a pediatric population, is readily understood by pediatric orthopaedists. However, there is a lack of research that demonstrates caregivers' awareness regarding pediatric orthopaedic patients' bone health, such as the importance of nutrition, sunlight exposure, and supplementation. This study aims to assess the knowledge base of caregivers of pediatric orthopaedic patients and to identify associations between bone health knowledge and demographic factors. It is hypothesized that this study will not only elucidate a general lack of knowledge regarding nutritional sources of vitamin D and calcium but will also clarify the populations in which this deficit is most pronounced. Methods: Caregivers of outpatient pediatric orthopaedic patients were asked to complete a study-specific questionnaire assessing their knowledge of sources of calcium and vitamin D. Possible scores on this assessment range from +8 to −12 with positive scores reflecting a better ability to identify sources of calcium and vitamin D. Associations between score and demographic factors were analyzed using multiple linear regression models. Results: A total of 184 caregivers were included for analysis. Caregiver race and current vitamin supplementation for their child were significant predictors of overall score when identifying sources of calcium and vitamin D. Hispanic/Latino participants scored significantly lower than Black participants by β = 1.75 (P = .010, 95% CI=[−3.08, −0.43]) and significantly lower than White participants by 2.24 (P .001, 95% CI=[−3.34, −1.14]). There was no significant difference in score when comparing Black and Caucasian participants (P = .426, 95% CI=[−1.70, 0.72]. Caregivers who did not provide their children with supplements had a significantly lower mean overall score by 1.142 (P = .017, 95% CI=[−2.078, −.206]) when compared to caregivers who did provide their children with supplements. The overall performance on the questionnaire was assessed to be low, with a standardized mean score of 1.51. One hundred and twenty three participants (66.85%) were in a positive score range, 45 participants (24.46%) were in a negative score range, and 16 participants (8.70%) scored a net of 0. Conclusion: There are substantial deficits in caregiver knowledge regarding sources of calcium and vitamin D with Hispanic/Latino caregivers scoring lower on our study questionnaire when compared to Black and Caucasian caregivers. Caregivers that provided supplements to their child tended to score higher on the questionnaire. Key Concepts: (1) The disparities that exist in pediatric bone health have been previously reported, yet the underlying cause for such disparities is varied and complex. (2) This study assessed caretaker knowledge on childhood nutrition, prompting individuals to identify key nutritional sources of vitamin D and calcium. (3) Across all study populations, there was room for increased awareness as well as a desire to learn more about calcium and vitamin D. (4) Further research investigating how social factors contribute to bone health, nutrition, and childhood supplementation is warranted. (5) Improving communication and education relating nutrition and bone health is an opportunity for community impact for orthopaedic providers. Level of Evidence: Level IV.